2020
DOI: 10.1002/mrd.23440
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidin B1 promotes in vitro maturation of pig oocytes by reducing oxidative stress

Abstract: Oxidative stress negatively affects the in vitro maturation (IVM) of oocytes. Procyanidin B1 (PB1) is a natural polyphenolic compound that has antioxidant properties. In this study, we investigated the effect of PB1 supplementation during IVM of porcine oocytes. Treatment with 100 μM PB1 significantly increased the MII oocytes rate (p <0.05), the parthenogenetic (PA) blastocyst rate (p <0.01) and the total cell number in the PA blastocyst (p < 0.01) which were cultured in regular in vitro culture (IVC) medium.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
(72 reference statements)
2
11
0
Order By: Relevance
“…As procyanidins increase cell viability, decrease ROS production and restrain oxidative stress in mammalian cells 35, 36 , we next interrogated whether similar or antioxidant effects can be traced in senescent cells exposed to PCC1. Surprisingly, we observed the opposite side, as senescent PSC27 cells displayed elevated ROS levels when treated by PCC1, making a sharp contrast to their proliferating counterparts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As procyanidins increase cell viability, decrease ROS production and restrain oxidative stress in mammalian cells 35, 36 , we next interrogated whether similar or antioxidant effects can be traced in senescent cells exposed to PCC1. Surprisingly, we observed the opposite side, as senescent PSC27 cells displayed elevated ROS levels when treated by PCC1, making a sharp contrast to their proliferating counterparts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Zhang et al reported that lower doses (5–25 µM) of naturally occurring phenolic compounds (rosmarinic acid) attenuated intracellular ROS levels in porcine oocytes and cumulus cells during IVM [ 59 ]. Moreover, low doses (100 µM) of the polyphenolic compound procyanidin, which is derived from plant sources, also decreased ROS production and apoptosis, while promoting the quality of oocytes and PA embryo development [ 60 ]. Therefore, it is ideal to investigate the anti-oxidative effects of MSmPNPs on the critical stage of IVP in porcine IVM and subsequent embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of previous studies [22,25,29], we can determine that PB1 is a small-molecule drug with antioxidant effects. In addition, we can confirm that it can improve the developmental ability of embryos during early development [29].…”
Section: Discussionmentioning
confidence: 99%
“…Procyanidin B1(PB1) is a small-molecule compound, extracted from a variety of plants [20][21][22][23], especially grapes [24][25][26], and it has strong antioxidant effects [22,24,[27][28][29]. The antioxidant function of PB1 works by reducing the LPS-induced production of ROS and inhibiting extracellular signal-regulated kinase (ERK)1/2 and IkB kinase beta (IKKb) activity [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation